1991
DOI: 10.1677/joe.0.1300469
|View full text |Cite
|
Sign up to set email alerts
|

The induction of a specific protease for insulin-like growth factor binding protein-3 in the circulation during severe illness

Abstract: The insulin-like growth factors (IGF-I and IGF-II) are almost completely bound in the circulation to specific binding proteins (IGFBPs). These IGFBPs appear to play a pivotal role in maintaining circulating levels and modulating the delivery of the IGFs to the tissues. A large proportion of the circulating IGFs are bound with high affinity to one of the binding proteins. IGFBP-3. The mechanism by which these IGFs are transferred from the circulatory pool to the tissue receptors is at present unclear. Recent st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
86
0

Year Published

1992
1992
2002
2002

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 209 publications
(90 citation statements)
references
References 13 publications
4
86
0
Order By: Relevance
“…The basal levels of IGF-I and -II produced by both the MCF-10A and the Hs578T cells, as measured by radioimmunoassays previously described (Taylor et al, 1990;Davies et al, 1991) were found to be lower than the detection limits of the assays and hence negligible in relation to the doses required for IGF responses in these cells (i.e. 51 ng ml 71 ; data not shown).…”
Section: Radioimmunoassaymentioning
confidence: 85%
“…The basal levels of IGF-I and -II produced by both the MCF-10A and the Hs578T cells, as measured by radioimmunoassays previously described (Taylor et al, 1990;Davies et al, 1991) were found to be lower than the detection limits of the assays and hence negligible in relation to the doses required for IGF responses in these cells (i.e. 51 ng ml 71 ; data not shown).…”
Section: Radioimmunoassaymentioning
confidence: 85%
“…The partial proteolysis of IGFBP-3 is detectable in normal serum (30), but has been reported to increase considerably in the postoperative phase (21)(22)(23) and during critical illness (24,25). In critically ill patients who had recently undergone surgery, Davies et al (25) reported this proteolytic activity to be strongly regulated by parenteral nutrition. However, in fasted healthy controls (age-and sex-matched), no IGFBP-3 proteolysis was observed, suggesting that other specific factors related to surgery are involved.…”
Section: Discussionmentioning
confidence: 99%
“…Plasma GH levels may also be low, as reported in cases of prolonged critical illness, thereby contributing to low plasma IGF-I levels (20). Partial proteolysis of IGFBP-3 has been reported to increase during the postoperative phase (21)(22)(23) and in critical illness (24,25), but the mechanisms regulating this process are poorly understood. Changes in the IGF system have not been thoroughly studied in ill, elderly subjects, in whom this system may be affected by both malnutrition and aging.…”
Section: Introductionmentioning
confidence: 99%
“…An increased IGFBP-3 protease activity has been described in certain pathological conditions like diabetes (Bereket et al, 1995), severe illness (Davies et al, 1991), but also in patients suffering from advanced malignancies, including breast cancer (Frost et al, 1996). If this also occurs for patients with early breast cancer, it could make total IGF-I an unreliable predictor of bioavailable IGF-I in these patients.…”
mentioning
confidence: 99%